Media Frames and Sustainability Mindsets: Implications for Green Digital Marketing in Indonesia - Ignasius Heri Satrya Wangsa (BIP's JURNAL BISNIS PERSPEKTIF, 2026)
This study examines how sustainability is framed in major Indonesian national online news media and how such framing contributes to the development of sustainability mindsets relevant to business practices and green consumer markets. Focusing on five leading platforms—Kompas.com, Detik.com, CNNIndonesia.com, Liputan6.com, and Tempo.co—this research conducts a qualitative content analysis of articles published between 2024 and 2025 that address sustainability in corporate strategy, environmental governance, green innovation, and ethical consumption. The findings reveal the presence of dominant frames such as environmental urgency, techno-optimism, regulatory accountability, and lifestyle engagement. For instance, Kompas.com and Tempo.co frequently feature analytical coverage on ESG policies, carbon reduction initiatives, and responsible investment, while Detik.com and Liputan6.com highlight consumer-friendly narratives on waste reduction, renewable products, and urban sustainability trends. CNNIndonesia.com offers policy-centered reporting that bridges state commitments and corporate transitions. These frames collectively shape public perception by normalizing sustainability as both a moral and economic imperative, thereby influencing how businesses position themselves and how consumers interpret green value propositions. The study underscores the strategic relevance of media framing for green digital marketing, suggesting that alignment with dominant media narratives enhances message resonance and public trust in sustainability campaigns.